DEVELOPMENT OF INTERACTIVE VIDEO-BASED LEARNING MEDIA ON THEMATIC LEARNING IN CLASS 4 SD - Ade Irmala Sandy; Rudi Erwandi; Tio Gusti Satria (Yayasan Citra Dharma Cindekia, 2021)
This study aims to produce the Development of Interactive Video-Based Learning Media in Thematic Learning in Grade 4 Elementary School. This research is a research and development using a 4-D model consisting of 4 stages, namely: the definition stage, the design stage, the development stage and the dissemination stage. The data collection technique of this research is based on the results of assessments by three experts, namely: material experts, media experts, and linguistsInteractive Video-based learning mediameet the valid criteria with an average score of 0.75 Classified as High Enough. At the practical stage of 1 teacher and small group test consisting of 6 students it was found thatInteractive Video-based learning media meet the practical criteria with an average score of 89.4. Based on the results of the study it can be concluded that the design Interactive Video-based learning media developed in this study proved to be valid and practical for the fourth grade students of SD Negeri 1 Tegalrejo.